Changing Bird Migration Patterns Have Potential to Enhance Dispersal of Alien Plants From Urban Centres - Deshpande, Purabi; Johansson, Niko; Kluen, Edward; Lehikoinen, Aleksi; Thorogood, Rose (Wiley, 2025)
There is increasing recognition that alien species may be ‘sleepers’, becoming invasive with favourable changes in conditions, yet these changes remain difficult to predict. As populations of frugivorous birds shift with urbanisation and climate change, they could provide dispersal services for introduced fruiting plants that have previously been considered benign. This is likely to be especially problematic at higher latitudes where bird migration phenologies are altering rapidly. However, any consequences for fruit dispersal have not yet been explored. Here, we use Helsinki, Finland, to investigate whether (i) streetscapes provide birds with a fruit resource that differs from urban forest fragments and (ii) the chances for dispersal of alien species (i.e., preferential consumption of native fruits). While there were both more fruits and birds in streetscapes (replicated across multiple years), fruits were not consumed preferentially according to origin. Additionally, seed analysis from faecal samples of blackbird Turdus merula L., a previously migratory but increasingly resident species, suggested that alien and native plants are equally likely to be dispersed. These results indicate that birds could be dispersing alien species more frequently than previously thought and highlight the complex effects of changing climates on potentially invasive species.